Il Partito comunista italiano e i regimi comunisti dell’Europa orientale attraverso la rivista “Rinascita” - SANTORO, Stefano (Studia Universitatis Babeș-Bolyai Historia, 2021)
The Italian Communist Party and the communist regimes of Eastern Europe through the magazine “Rinascita”. The cultural magazine of the Italian Communist Party “Rinascita” was published from 1944 to 1991, thus following the evolution of that party from the post-WWII to its self-dissolution. Through an analysis of the articles published in the magazine, this contribution studies the evolution of the image of the communist regimes of Eastern Europe among the Italian communists, retracing the strategic and ideological changes that characterized the Pci, along a difficult path that from the cult of Stalin eventually came to social democracy. Article history: Received 15.11.2021; Revised 7.12.2021; Accepted 20.12.2021; Available online 13.04.2022. Rezumat: Partidul Comunist Italian şi regimurile comuniste din Europa de Est prin intermediul revistei “Rinascita”. Revista culturală a Partidului comunist italian “Rinascita” a apărut între 1944 şi 1991, urmărind astfel evoluţia acelui partid de la cel de-al Doilea Război Mondial până la autodizolvarea sa. Printr-o analiză a articolelor publicate în revistă, această lucrare studiază evoluţia imaginii regimurilor comuniste din Europa de Est în rândul comuniştilor italieni, reluând schimbările strategice şi ideologice care au caracterizat Pci, de-a lungul unui drum anevoios care de la cult a lui Stalin a ajuns în cele din urmă la social-democraţia. Cuvinte cheie: Revista “Rinascita”; Partidul comunist italian; Europa de Est; “Socialismul real”.